Towards sustainable diet: An inquiry of plant-based diet using protective motivation theory - Chin, Wei Chong; Wendy Teoh, Ming Yen; Ojo, Adedapo Oluwaseyi (Elsevier B.V., 2025)
This study explores the motivators and barriers in influencing Malaysian university students’ intentions to adopt plant-based diets with protective motivation theory. A cross-sectional survey involving 340 students from ten Malaysian universities was conducted using a structured questionnaire based on established scales for threat appraisal (perceived severity, vulnerability, intrinsic and extrinsic rewards), and coping appraisal (perceived response efficacy, self-efficacy and cost). The findings indicate that individuals with lower intrinsic rewards and higher response efficacy and self-efficacy are more likely to demonstrate the intent to adopt a plant-based diet. Gender differences tests reveal that males tend to perceive higher levels of intrinsic and extrinsic rewards for a plant-based diet, while females have higher self-efficacy. By leveraging these insights, stakeholders can foster sustainable and healthy eating practices among young adults, contributing to broader environmental and public health objectives.